PENINGKATAN KEMAMPUAN MEMBACA SISWA MELALUI PERTANYAAN WEB EXE DIHUBUNGKAN DENGAN ANIMASI - Arpandi Arpandi (UNMUHBABEL Press, 2019)
The goal of this Classroom Action Research is to increase students’ reading ability signed by the ability of students to answer the main idea, detail text, cause and effect, and the description of the text conclusion. The writer uses learning media through web exe related to animation by multiple questions. There are three cycles with four procedures; planning, acting, observing and reflecting. The result is significant increasing of vocabularies and students’ reading ability. It is signed by firstly at the first cycle the average of students’ test score 72,1 for XII IPS 2 compared with before cycle 63,7, the increasing 8,4 point. For XII IPS 3 there is increasing 12 point, 76,8 compared with 64,8. At the second cycle, class XII IPS 2 got 74,5 with increasing 2,4, and class XII IPS 3 got 76,9 with increasing 0,1 point. At the third cycle, class XII IPS 2 got 78,2 with increasing 3,7, and class XII IPS 3 got 82,9 with increasing 6,0 point. Secondly there are 28 students from XII IPS 2 and 30 students from XII IPS 3 getting score equal or more than 75. The last conclusion the teaching media using web.exe related to animation question is worthy to use, because it can increase students’ vocabularies and reading ability.